Characterizing soil erosion potential using electrical resistivity imaging - Karim, Md Zahidul (Kansas State University, 2016)
The erosion rate, or erodibility, of soil depends on many soil characteristics including: plasticity, water content, grain size, percent clay, compaction, and shear strength. Many of these characteristics also influence soil in situ bulk electrical resistivity (ER) measurements. The objective of this study was to characterize soil erosion potential by correlating the in situ ER of soil with erodibility measured in the Kansas State University Erosion Function Apparatus (KSU-EFA). ER surveys were conducted at eleven bridge sites. Soil samples were also collected at each site with a drill rig from the surface to three meters using thin-walled Shelby tubes. Five samples were collected at each site, tested in the KSU-EFA, and classified according to the Unified Soil Classification System. Analysis showed that the rapid in situ data obtained from an ER survey can be used to categorize the level of erodibility. As such, ER surveys may be used to characterize the soils at future bridge sites or prioritize existing bridges for additional testing to measure the scour potential. Moreover, ER surveys may be used to determine which existing bridges should be closed or closely monitored for scour potential during a flood event. Analytical models to predict critical shear stress using ER and other soil parameters were constructed.
Keywords: Soil erosion; Scour; Electrical resistivity; Kansas